THE INFLUENCE OF PRODUCT QUALITY ON PURCHASE DECISION THROUGH BRAND IMAGE AND WORD OF MOUTH AS MEDIATING VARIABLES ON OPPO SMARTPHONE CONSUMERS IN MALANG CITY - Havisfal Alviansyah; Sudarmiatin; Wening Patmi Rahayu (CV. RADJA PUBLIKA, 2024)
Humans as social creatures certainly need interaction with other humans, in this modern era there are many ways for humans to communicate with each other, one of which is using smartphones. In this study, we will discuss how consumer behavior in making purchases of Oppo smartphones. The research method used in this study is a quantitative method. The partial least square (PLS) data analysis method is used in this investigation. PLS is a structural equation modeling (SEM) model that uses a component-based or variance-based approach. From the results of the Bootstrapping analysis, all hypotheses were obtained with a P-value below 0.05 which means that all hypotheses were accepted. The results of this analysis also show that the Brad Image and Word of Mouth variables are able to mediate the influence of product quality on purchase decisions.